Twenty-five years of the Journal of Business Economics and Management: a bibliometric overview - Pacheco-Cedeño, Ana Cristina; Alfaro-García, Víctor G.; Merigó, José M.; Davidavičienė, Vida (Journal of Business Economics and Management, 2026)
The Journal of Business Economics and Management (JBEM) was established in 2003 as a continuation of the Almanach des praktischen Managements in Mittel- und Ost-Europa, that was founded in 1999. Today, it has evolved into a recognised platform at the intersection of economics, management, and decision science. This study conducts a comprehensive bibliometric analysis of JBEM’s publication record, employing a dual-database approach that examines 1,182 articles published between 2003 and 2024 in Scopus and 1,020 documents in Web of Science from 2007 to 2024. Using VOSviewer for network mapping, the analysis reveals a stable intellectual core focused on multi-criteria decision-making methods, alongside a growing emphasis on sustainability, ESG, and corporate responsibility. Ginevičius, Tvaronavičiene, and Zavadskas emerge as the most prolific authors, while Vilnius Gediminas Technical University, Bucharest University of Economic Studies, and Vilnius University lead the institutional contributions. At the country level, Lithuania, China, and Spain are the main contributors. The findings offer relevant insights for understanding how thematic priorities evolve, and inform future expected research and journal development. From a practical perspective, the results may guide editors and researchers in identifying key contributors and collaboration networks. This study’s originality lies in the integration of dual-database coverage with the combined use of quantitative indicators and visual analysis, offering a richer longitudinal perspective on the journal’s evolution.